Clinical and neurological features of the course and cognitive impairment in orthostatic hypotension in patients with neurodegenerative diseases - Slobodin, Tatyana; Goreva, Ganna; Golovchenko, Yuriy; Klymenko, Olxandr (ScienceRise: Medical Science, 2017)
Aim: To optimize the diagnostics of cognitive impairments in patients with neurodegenerative diseases and orthostatic hypotension, based on the estimation of the character of interrelations between clinical-pathogenetic features, degree of cognitive functions impairments and several indices of hemodynamics. Materials and methods. There was realized the general clinical, neurological examination, neuropsychological testing: MMSE, MoCA, FAB, test of memorization of 12 words, drawing of a watch, phonetic speed of speech, semantic speed of speech; orthostatic test. There were examined 105 patients: the first group – patients with AD (33 patients), the second – with PD (35 patients), the third, control group (37 examined persons) – practically healthy people. Groups 1 and 2 were divided in the subgroup А (with orthostatic hypotension) and the subgroup B (with the normal orthostatic reaction). Results. The clinical picture of patients of the subgroup A demonstrated complaints, typical for OH episodes, reliably more often than the one of the subgroup B and control. Complaints for the memory worsening and difficulties at trying to choose a proper word, falling were observed statistically reliably more often in patients with PD and OH. Positive axial reflexes, revival of tendon and periosteal reflexes were revealed more often in the subgroup 1A than in 1B at the neurological examination; in the subgroup 2А – nystagmus, positive axial reflexes, postural instability. According to the results of the neuropsychological test, points of MoCA scale, test of semantic speed of speech, memorization of 12 words; memory and attention domains by subtests of MoCA scale in patients of 1A group were statistically reliably less than in 1B subgroup. Points of patients of 2A subgroup were statistically reliably less than in 2B subgroup by MoCA, FAB scales, by the test of phonetic speed of speech, semantic speed of speech, memorization of 12 words; by subtests of ruling functions, memory and attention of MoCA scale . Conclusions 1. MoCA scale, test of drawing a watch, test of memorization of 12 words, test for semantic and phonetic speed of speech turned out to be more sensitive at orthostatic hypotension. 2. At orthostatic hypotension impairments in domains of memory, attention, speech, occur more often in patients with Alzheimer’s disease, in ones with Parkinson disease – impairments of memory, attention, ruling functions, thinking